Flavocytochrome b2-Based Enzymatic Method of L-Lactate Assay in Food Products - Oleh Smutok; Maria Karkovska; Halyna Smutok; Mykhailo Gonchar (The Scientific World Journal)
L-lactate, a key metabolite of the anaerobic glycolytic pathway, plays an important role as a biomarker in medicine, in the nutritional sector and food quality control. For these reasons, there is a need for very specific, sensitive, and simple analytical methods for the accurate L-lactate measuring. A new highly selective enzymatic method for L-lactate determination based on the use of flavocytochrome b2 (EC 1.1.2.3; FC b2) isolated from the recombinant strain of the yeast Hansenula polymorpha has been developed. A proposed enzymatic method exploits an enzymatic oxidation of L-lactate to pyruvate coupled with nitrotetrazolium blue (NTZB) reduction to a colored product, formazan. The maximal absorption peak of the colored product is near λ=525 nm and the linear range is observed in the interval 0.005–0.14 mM of L-lactate. The main advantages of the proposed method when compared to the LDH-based routine approaches are a higher sensitivity (2.0 μM of L-lactate), simple procedure of analysis, usage of inexpensive, nontoxic reagents, and small amount of the enzyme. Enzymatic oxidation of L-lactate catalyzed by flavocytochrome b2 and coupled with formazan production from nitrotetrazolium blue was shown to be used for L-lactate assay in food samples. A high correlation between results of the proposed method and reference ones proves the possibility to use flavocytochrome b2-catalysed reaction for enzymatic measurement of L-lactate in biotechnology and food chemistry.